A case of metoclopramide-induced oculogyric crisis in a schizophrenic patient under anticholinergic therapy - Begüm Aygen Gümüş; Hülya Ertekin (SERNEV, 2022)
Introduction: Oculogyric crisis (OGC) is a dystonic reaction characterized as conjugate and typically upward deviation of the eyes lasting from seconds to hours which is seen as an uncommon neurologic manifestation. Metoclopramide is a prokinetic agent that is frequently prescribed in the treatment of nausea, vomiting prophylaxis, and vomiting. One of the side effects after metoclopramide treatment is acute dystonic reactions.Case Presentation: We report a case of metoclopramide-induced OGC despite the anticholinergic treatment in patient diagnosed with schizophrenia.Conclusions: Metoclopramide-induced OGC and other acute dystonic reactions may be more frequent than expected. Therefore, clinicians should monitor patients closely during treatment with metoclopramide and necessary precautions should be taken for these reactions.Keywords: Metoclopramide, oculogyric crisis, side effect, schizophrenia